Guaramiranga: propostas de zoneamento e manejo ambiental - Bastos, Frederico Holanda (2005)
Humid mountains of the Ceará favor to propitiate a bigger agricultural production and demographic concentration, because presenting edafo-climatic conditions better than was found in the semidries of sertaneja depressions. The Baturité’s set mountains in particular, constitutes one of more expressive relief compartment next to the coast. Inserted in this set mountains, the Guaramiranga municipal district has been detached in the last years for the increase of the real estate speculation in function of its natural potentialities and many cultural events of national reach that happened there. Some environmental problems related to the improper use of the ground, have made with that this municipal district came to be a excellent area of scientific community interest. In this way, the present research has as objective to analyze and to make the compartment of the Guaramiranga municipal district, following a geoambiental perspective, looking for to identify the main problems, limitations and potentialities. After to consider procedure of environmental use directed to a sustainable development. This research has a interdiscipline character, integrating of synthetic form all the components and environmental processes evidenced in the study area. In this form, Guaramiranga was cartographic subdivided with a the aid of the geoprocessing, in three environmental units with distinct geoambiental characteristics: the east side, the humid plateau and west side. The east side and the humid plateau have currently good edafo-climatic conditions, with a perenifolia forest and relief strong dissected where happened processes of removal of the vegetation. In the west side the humidity decrease makes with that it presents similar conditions of caatinga, with shallow soil blanketed by the dry forest and occurrence of rocky blooming. The environmental problems of the three environmental units of the mountain had been deforestation, cultivation with rudimentary techniques in areas of accented declivitous, cultural events with not appropriate infrastructure and deforestation in the springs of the rivers.It is of basic importance that the areas of permanent preservation are really proteges, having to be created incentives so that the production of the ecological coffee and forestry start to be inserted in the local economy.The public administration must exert inspect paper, including politics directed toward the income creation and social inclusion.The environmental education must be boarded in the schools and must be made training so that the small agriculturists can use the ground in appropriate way.Of this form a sustainable development can be searched so that the future generations also can usufruct of the beauties of Guaramiranga.